2021
DOI: 10.3390/su132111697
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Analysis of Applying Blockchain Technology to Forestry Carbon Sink Projects Based on the Differential Game Model

Abstract: As an important way to reduce emission, forestry carbon sink (FCS) has not been implemented effectively. Therefore, this paper aims to analyze the effectiveness and mechanism of applying blockchain technology in FCS projects by utilizing the differential game model. A Stackelberg differential game model between forest farmers and emission-controlled enterprises (ECEs) is developed to analyze the optimal emission reduction efforts and the optimal trajectory of forest farmers and ECEs before and after introducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…i.e., Equation (15) does not hold. In this case, considering regulatory costs, emissionproducing enterprises decrease their monitoring of third-party environmental service providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…i.e., Equation (15) does not hold. In this case, considering regulatory costs, emissionproducing enterprises decrease their monitoring of third-party environmental service providers.…”
Section: Discussionmentioning
confidence: 99%
“…The second is the study of the relevant factors affecting third-party governance and their policy effects [8][9][10]. It was found that direct performance, process-management effectiveness, and stakeholder satisfaction with cooperation all influence the decision making of third-party environmental service providers [11,12], and that pollution taxes and incentivization policies positively affect pollution governance [13][14][15][16]. The third encompasses the barriers and dilemmas of thirdparty environmental-service-provider governance, which were explored by constructing theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the smart contract can effectively prevent contract performance risk. It has gradually played an important role in responding to environmental and sustainability challenges [51], monitoring green production [52], increasing willingness to reduce carbon emissions [53], reducing energy waste, encouraging the use of green energy, and decreasing the proportion of fossil fuels [54], creating a more friendly environment for the whole energy industry [47], improving the transparency in the energy trading process [48], improving the efficiency of the circular economy, achieving trust construction and effective incentives, and promoting the transformation of the 'information Internet' to the 'value Internet' [55], which provides extensive support for environmental management and sustainable development [56]. With the maturity of blockchain technology, its application in different industries, such as finance, logistics, supply chains, and enterprise production, has been achieved.…”
Section: Blockchain Technologymentioning
confidence: 99%
“…Kim, S et al attempted to use blockchain technology to make a trust endorsement for carbon rights trading to ensure the security of the transaction, and therefore, used blockchain technology to construct a carbon rights trading authentication system [18]. Sun, R et al investigated the form and effect of blockchain technology in carbon rights trading and pointed out that blockchain technology was superior to the form of ECE in terms of reducing costs and improving the efficiency of emission reduction [19]. Yan, M. et al introduced blockchain technology into the microgrid carbon trading market, combining the cooperative game framework and the algorithm of column-constrained generating conditions to achieve the optimization of carbon energy trading and promote the users' willingness to trade energy and carbon rights independently [20].…”
Section: Introductionmentioning
confidence: 99%